Secretin modulates appetite via brown adipose tissue-brain axis - Sun Lihua; Laurila Sanna; Lahesmaa Minna; Rebelos Eleni; Virtanen Kirsi A.; Schnabl Katharina; Klingenspor Martin; Nummenmaa Lauri; Nuutila Pirjo (SPRINGER, 2025)
Purpose
Secretin activates brown adipose tissue (BAT) and induces satiation in both mice and humans. However, the exact brain mechanism of this satiety inducing, secretin-mediated gut-BAT-brain axis is largely unknown.
Methods and results
In this placebo-controlled, single-blinded neuroimaging study, firstly using [18F]-fluorodeoxyglucose (FDG) PET measures (n = 15), we established that secretin modulated brain glucose consumption through the BAT-brain axis. Predominantly, we found that BAT and caudate glucose uptake levels were negatively correlated (r = -0.54, p = 0.037) during secretin but not placebo condition. Then, using functional magnetic resonance imaging (fMRI; n = 14), we found that secretin improved inhibitory control and downregulated the brain response to appetizing food images. Finally, in a PET-fMRI fusion analysis (n = 10), we disclosed the patterned correspondence between caudate glucose uptake and neuroactivity to reward and inhibition, showing that the secretin-induced neurometabolic coupling patterns promoted satiation.
Conclusion
These findings suggest that secretin may modulate the BAT-brain metabolic crosstalk and subsequently the neurometabolic coupling to induce satiation. The study advances our understanding of the secretin signaling in motivated eating behavior and highlights the potential role of secretin in treating eating disorders and obesity.